2012
DOI: 10.1002/app.38232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vinyl isocyanate coupling agent on the tensile properties of Kraft fiber‐unsaturated polyester composites

Abstract: A vinyl isocyanate (VI) synthesized from toluene diisocyanate and 2-hydroxyethyl methacrylate was used as a novel coupling agent to obtain strong chemical interfacial adhesion and therefore, improve the tensile properties of Kraft fiber-reinforced unsaturated polyester (UPE) composites. Results characterized by fourier transform infrared spectroscopy (FTIR), dynamic mechanical analysis (DMA), and scanning electron microscope (SEM) indicated that the novel coupling agent VI had a significant effect on the tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The reason was that the surface of the aramid fiber was smooth, there was a lack of polar groups and chemical activity. In generally, epoxy resin coating was used as the surface treatment method of the aramid fiber . Thus, the elastic modulus of the interphase varied between E e = 3 GPa (fiber coated with the epoxy resin) and E m = 2 MPa (rubber matrix).…”
Section: Resultsmentioning
confidence: 99%
“…The reason was that the surface of the aramid fiber was smooth, there was a lack of polar groups and chemical activity. In generally, epoxy resin coating was used as the surface treatment method of the aramid fiber . Thus, the elastic modulus of the interphase varied between E e = 3 GPa (fiber coated with the epoxy resin) and E m = 2 MPa (rubber matrix).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the addition of 5% polyisocyanate as a crosslinking agent could result in a satisfactory increase in the tensile properties, whereas a further increase of polyisocyanate content did not bring about any improvements. This may be attributed to a saturation of the crosslinking efficiency of the polyisocyanate with the kraft fiber-polyester interfaces (Gao et al 2013). Considering the higher cost of polyisocyanate crosslinker (about US$2.90/kg) when compared to the unsaturated polyester resin (about US$1.94/kg), the optimal polyisocyanate level as a crosslinking agent was determined to be 5%, which yields an acceptable mechanical improvement while maintaining a low composite cost.…”
Section: Fig 1 Sem Micrographs Of Alkali Pretreated Kraft Fibers (mentioning
confidence: 99%
“…To fully make use of the wood scrap with more value added, environmental friendly bio‐composites may offer a solution by combining the modified soybean protein with the wood flour or wood fiber . Compared with lignocellulosic fibers, the low‐aspect‐ratio wood flours as reinforcement of composite have some advantages such as low cost, ease to obtain and process from wood scrap, less challenging to obtain proper blend with polymer matrix, etc …”
Section: Introductionmentioning
confidence: 99%
“…Interfacial adhesion is known to have a significant effect on the properties of composites. It has been confirmed that the poor interfacial adhesion could be improved using compatibilizers or crosslinkers to form bridges of chemical bonds between the wood reinforcements and the polymer matrices . Glyoxal, glutaraldehyde, and polyamidoamine‐epichlorohydrin (PAE) are the most commonly used crosslinking agents for soybean protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation